RESEARCH OF NATIONAL CULTURE AND ART HISTORY ON THE EVE OF INDEPENDENCE (CINEMA AND THEATER FOR EXAMPLE) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
: In this article, the study of the history of culture and the independent study of the history of culture and art, and the material and technical base of the national cinema, theater, and art through them to see the past, history, and Uzbek the peculiarities of the revival and development of the creativity of the people are highlighted.